2016
DOI: 10.5123/s2176-62232016000500024
|View full text |Cite
|
Sign up to set email alerts
|

Citomegalovírus: epidemiologia baseada em dados de soroprevalência

Abstract: RESUMOO citomegalovírus humano (HCMV) é um dos principais agentes causadores de diversos agravos mórbidos nos períodos pré e pós-natal. De acordo com os dados soroepidemiológicos, esse agente é altamente prevalente no mundo com diferentes taxas de infecção nos diversos estratos da sociedade e regiões geográficas. A elevada prevalência está principalmente associada a fatores socioeconômicos, aos maus hábitos de higiene, às péssimas condições de saneamento básico e ao nível cultural das populações, sobretudo aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
2
0
2
Order By: Relevance
“…It is estimated that the seroprevalence of the Epstein-Barr virus in the world population is 90%-95% (70) . The same trend is observed in relation to CMV, with seroprevalence ranging from 80 to 100% in emerging countries (71) .…”
Section: • Laboratory Criteria For Donor Selectionsupporting
confidence: 71%
“…It is estimated that the seroprevalence of the Epstein-Barr virus in the world population is 90%-95% (70) . The same trend is observed in relation to CMV, with seroprevalence ranging from 80 to 100% in emerging countries (71) .…”
Section: • Laboratory Criteria For Donor Selectionsupporting
confidence: 71%
“…Given the mean age of our sample ranging from 20 to 81 years (45.9 ± 16.8 years), the absolute positivity rate for IgG showed the expected CMV prevalence in Southern Brazil [ 3 – 5 ]. We found that, despite the high prevalence of anti-CMV IgG, which indicates previous infection and latency (IgG + and IgM-), antibody titers did not correlate with severity of COVID-19 or humoral responses to SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Cytomegalovirus represents one of the most common infections globally, with a prevalence ranging from 50 to 95% depending on age and socioeconomic status [ 2 ]. Studies from Southern Brazil [ 3 – 5 ] show an 88–98% IgG prevalence in adults below 55 years old, and 100% in older individuals, with anti-CMV IgM present in 2.4% of the adult population, most of them under 35 years old and probably representing new infections [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A figura 2 mostra a frequência com que estes sinais são apontados nos trabalhos revisados. Ressalta-se que estas evidências clínicas podem estar ausentes ao nascimento, caracterizando como manifestações tardias, além do vírus poder ser adquirido durante a passagem pelo canal do parto ou por meio da amamentação (MATOS, MEYER, LIMA, 2011;FERREIRA et al, 2017;SILVA, 2016). A presente pesquisa encontrou algumas objeções em sua construção, pois há um número reduzido de estudos na área, e quando encontrados, os artigos são ultrapassados quanto a série histórica definida.…”
Section: Revistaunclassified